Role of Microcredit in urban poverty alleviation: a case study of shakti foundation for disadvantaged women - Chowdhury, Md. Wohid (BRAC University, 2010)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master of Development Studies, 2007.